(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this paper we study a problem at functional analysis, it is the inclusion of function spaces. Especially we study the inclusion of Orlicz-Modulation spaces 15Mد•Rd"> associated to Orlicz space which is defined by the dependence of young function, so we study some inclusion cases for this space for different cases of young function. We also study a special case of the inclusion between Modulation space 15Ma,bp,qRd"> and Orlicz-Modulation 15Mد•Rd"> , which is the Orlicz-Modulation space to young’s function 15د•x=1+xln1+x- x"> .